The Development of Learning Media “E-Writing” to Develop Students’ Writing Skill of English Education Department - Indrayani, Ninuk (Journal of Language Intelligence and Culture, 2020)
This study aimed at developing an appropriate electronic learning media named E-Writing to improve students’ writing skill of English Education Department. This media will be the solution of students’ difficulties in writing activities especially as a guidence for writing task and activities. That is why this research is going to develop a media which based on the needs of analysis to make the learning process of writing skill become effective. This research is developed based on the Design and Development (D&D) model. The data obtained from the experts’ evaluation result. All data are both analyzed qualitatively and quantitatively using mean score and alpha Cronbach formula. The result of this study suggested that E-Writing can be such a beneficial media for students’ writing development.